Lipschitz stability for an inverse source scattering problem at a fixed frequency*The research of PL is supported in part by the NSF Grant DMS-1912704. (5th January 2021) - Li, Peijun; Zhai, Jian; Zhao, Yue
Abstract: This paper is concerned with an inverse source problem for the three-dimensional Helmholtz equation by a single boundary measurement at a fixed frequency. We show the uniqueness and a Lipschitz-type stability estimate under the assumption that the source function is piecewise constant on a domain which is made of a union of disjoint convex polyhedral subdomains.